THE UNION AND EMPLOYER - Marina I. Skripnikova (Plekhanov Russian University of Economics, 2018)
The article explains the notions ‘trade union’ and ‘employer’. Historic review of the trade union movement in Russia is described. Trade  unions were legalized in Western countries in the 30-90-s of the 19- th century, while in Russia it took place on the turn of 19th – 20th  centuries. Changes in the union movement after the October  revolution 1917 are shown, such as new responsibilities of socialist  trade union organizations, organization of labour socialist  competition, educational work. In 1921 the newspaper ‘Trud’ was  published, which is a body of the All-Union Central Council of Trade  Unions. In different periods the role of trade unions increased and  dropped. Nowadays trade unions acquired organizational  independence. The work of trade unions is regulated by the  Constitution of the Russian Federation. The government of Moscow, Moscow associations of trade unions and Moscow associations of employers concluded a three-sided agreement in order to guarantee  the interests of employees, employers and bodies of executive power in social and labour relations. The trade union organization of the  Russian Plekhanov University of Economics and the University  administration concluded a collective bargaining, which takes into  account specific features of the University and coordinates the parties’ interests in acute problems.